Abnormal Uterine Bleeding in Adolescent - Evelyne Theresia; Andreas Cristopher; Melissa Edelweishia (Indonesian Journal of Obstetrics & Gynecology Science)
AbstractAbnormal uterine bleeding (AUB) is a frequent cause of visits to health care provider during adolescent period. Heavy menstrual bleeding is the most frequent clinical presentation of AUB. This condition particularly worrisome in this group not only when it occurs at menarche, but also anytime afterward when bleeding lasts longer than 7 days, blood loss is greater than 80 mL per cycle, or other warning signs that indicate a history of heavy bleeding such as anemia. Careful history and examination can help elucidate the best next steps for workup and management. The primary goal of treatment is prevention of hemodynamic instability. Therefore, assessing the severity and cause of bleeding is important. Therapeutic approach in the acute period should be established according to the degree of anemia and amount of flow. Treatment options for medical care of AUB generally include hormonal, nonhormonal and surgery. Additionally, long-term management with hormonal therapy in patients with severe uterine bleeding is known to be safe for developing HPO axis.Perdarahan Uterus Abnormal pada RemajaAbstrakPerdarahan uterus abnormal (PUA) sering menjadi penyebab kunjungan ke penyedia layanan kesehatan selama masa remaja. Perdarahan menstruasi yang berat adalah gambaran klinis yang paling sering dari AUB. Kondisi ini sangat mengkhawatirkan para remaja yang terjadi bukan hanya saat menarche, tetapi juga bila perdarahan berlangsung lebih dari 7 hari, kehilangan darah lebih dari 80 mL per siklus, atau gejala lain yang menunjukkan riwayat perdarahan berat seperti anemia. Anamnesa dan pemeriksaan yang cermat dapat membantu menentukan langkah selanjutnya untuk pemeriksaan lanjutan dan penatalaksanaan. Tujuan utama penatalaksanaan adalah untuk mencegah ketidakstabilan hemodinamik. Oleh karena itu, menilai tingkat keparahan dan penyebab perdarahan sangat penting. Pendekatan terapeutik pada periode akut harus disesuai dengan derajat anemia dan jumlah perdarahan. Pilihan pengobatan untuk perawatan medis pada PUA  umumnya termasuk hormonal, nonhormonal dan pembedahan. Selain itu, manajemen jangka panjang dengan terapi hormonal pada pasien dengan perdarahan uterus yang parah diketahui aman untuk perkembangan aksis HPO.Kata kunci: Perdarahan uterus abnormal, remaja, menstruasi berat